Application Of Particle Swarm Optimization Algorithm In Information Systems Class Scheduling SMK Panca Budi 1 Medan - hindra Syaputra (Yayasan Sinergi Multidimensi Kreatif, 2024)
The class scheduling information system with the Particle Swarm Optimization Algorithm method at SMK Panca Budi 1 Medan is the division of student subject time scheduling. Good class scheduling and meeting all the conditions where teachers teach in two majors is one of the things that ensures the smooth implementation of teaching and learning activities. Using another approach, namely the PSO Algorithm Method, is expected to be useful and able to provide understanding and convenience to users to make class scheduling reports into the class scheduling system at SMK Panca Budi 1 Medan, which produces class scheduling reports in an arranged manner and does not cause clashes between teachers who teach in both departments.